Purification and characterization of a nitrilase from Aspergillus niger K10 - Kaplan, Ondrej; Vejvoda, Vojtech; Plíhal, Ondrej; Pompach, Petr; Kavan, Daniel; Bojarová, Pavla; Bezouska, Karel; Macková, Martina; Cantarella, Maria; Jirků, Vladimír; Kren, Vladimír; Martínková, Ludmila (Applied microbiology and biotechnology, 2006)
Aspergillus niger K10 cultivated on 2-cyanopyridine produced high levels of an intracellular nitrilase, which was partially purified (18.6-fold) with a 24% yield. The N-terminal amino acid sequence of the enzyme was highly homologous with that of a putative nitrilase from Aspergillus fumigatus Af293. The enzyme was copurified with two proteins, the N-terminal amino acid sequences of which revealed high homology with those of hsp60 and an ubiquitin-conjugating enzyme. The nitrilase exhibited maximum activity (91.6 U mg(-1)) at 45 degrees C and pH 8.0. Its preferred substrates, in the descending order, were 4-cyanopyridine, benzonitrile, 1,4-dicyanobenzene, thiophen-2-acetonitrile, 3-chlorobenzonitrile, 3-cyanopyridine, and 4-chlorobenzonitrile. Formation of amides as by-products was most intensive, in the descending order, for 2-cyanopyridine, 4-chlorobenzonitrile, 4-cyanopyridine, and 1,4-dicyanobenzene. The enzyme stability was markedly improved in the presence of D: -sorbitol or xylitol (20% w/v each). p-Hydroxymercuribenzoate and heavy metal ions were the most powerful inhibitors of the enzyme.
Keywords: molekulární sekvence - údaje; sekvence aminokyselin; teplota; Amino Acid Sequence; Aspergillus fumigatus; Aminohydrolases; Hydrogen-Ion Concentration; aminohydrolasy; koncentrace vodíkových iontů; sekvenční homologie aminokyselin; Enzyme Stability; Substrate Specificity; Temperature; substrátová specifita; Sequence Homology, Amino Acid; stabilita enzymů; Aspergillus niger; Molecular Sequence Data